Determinants Of Patient Satisfaction With Hospital-Based Homecare Services - Elita Novriana Enisa; Annisa Nurida; Djazuly Chalidyanto; Effita Piscesiana; Hendra Rakhma (PT.Mantaya Idea Batara, 2025)
Background: Homecare services play an essential role in supporting continuity of care after hospital discharge. Patient satisfaction is widely recognized as a measure of healthcare service quality and effectiveness. Objective: This study aimed to analyze the determinants of patient satisfaction with homecare services at a teaching hospital in Indonesia. Methods: A cross-sectional study was conducted involving 32 patients who received homecare services between July 2025 and March 2026. Data were collected using a structured questionnaire. Patient satisfaction was treated as the dependent variable, while cost, competence, friendliness, responsiveness, and ease of procedures were included as independent variables. Multiple linear regression analysis was applied to identify significant determinants. Results: The model demonstrated strong explanatory power (R² = 0.814; p < 0.001). Competence (β = 0.540; p < 0.001) and friendliness (β = 0.385; p = 0.008) were identified as significant determinants of patient satisfaction. In contrast, cost, responsiveness, and procedural ease were not statistically significant. Conclusion: Patient satisfaction in homecare services is primarily influenced by the competence and interpersonal qualities of healthcare providers.Strengthening human resource capacity is essential to improve service quality.